Upbeat nystagmus in a patient with a small medullary infarct. - Munro, N A (1993)
A 43 year old man presented with decreased sensitivity in the left side of the face and both upper limbs, and with upbeat nystagmus and skew deviation. MRI demonstrated a well defined lesion compatible with an infarct in the left side of the medulla, caudal and ventral to the vestibular nuclei, possibly involving the most caudal of the perihypoglossal nuclei, the nucleus intercalatus. Ocular motor studies, using an infrared system, showed that the nystagmus slow phase decayed exponentially, suggesting a failure of integration for vertical eye movements. Vertical integration might, therefore, be performed partly in the nucleus intercalatus.